Development of Chemical Learning Electronic Module Based on Multiple Representation in The Redox Topic - Septian Arfan; Nurfina Aznam (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2023)
The advent of the COVID-19 pandemic in 2020 significantly shifted educational paradigms, necessitating the adoption of online learning modalities. This study, rooted in the contextual changes brought by the pandemic, aimed to evaluate the effectiveness, quality, and impact of a Mixed Reality (MR) e-module on redox reaction topics in a high school setting. The research followed a 4D model (Define, Design, Develop, Disseminate) but was confined to the development phase.Conducted in a High School in Yogyakarta, Indonesia, this study involved 98 students (30 from grade 12 and 68 from grade 11), 3 teachers, and 2 validators. The research methodology included pre-tests and post-tests, alongside questionnaires to gather data. Descriptive statistical analysis was employed to process the assessments from validators, teachers, student responses, and test results.The field trial results indicated that the MR e-module for chemistry learning was deemed satisfactory and effective by the respondents. The analysis of the test of between-subject effect revealed no significant differences in interest and pre-test learning achievement between control and experimental groups. However, post-test results showed notable differences in interest and learning achievements, favoring the experimental group exposed to the MR e-module.The effectiveness of the MR e-module was quantified using partial eta squared calculations. The MR e-module contributed 25.7% effectively to both learning interest and achievement. When considered separately, the contribution was 2.7% for learning interest and 21.9% for learning achievement. These findings underscore the potential of MR e-modules as valuable educational tools, enhancing both student engagement and academic performance in online learning environments during the COVID-19 pandemic.